Accelerating Methane Reductions in Rice Production Systems Through Market-Based Mechanisms: Insight from Farmer Surveys and Choice Experiments in Philippines - Villanueva, Donald B.; Labios, Jade Ruth; Pajadan, Karen M.; Cabrera, Ellanie; Malana, Xyla Mae L.; Revicoy, Riela Rose R.; Mirzabaev, Alisher (International Rice Research Institute, 2025)
"Rice cultivation is a major source of methane emissions and consumes large amounts of water, making it a critical area for climate adaptation and mitigation in agriculture. In response, the Philippine Government aims to scale up the use of Alternate Wetting and Drying (AWD) across 3.21 million hectares of irrigated rice land, with an estimated emissions reduction of about 62.8 MtCO₂e1 between 2020- 2030. Currently, the adoption of AWD and other lowemission rice (LER) practices still remains limited. Rice farmers from Nueva Ecija (Luzon), Iloilo (Visayas), and Davao del Sur (Mindanao) were surveyed to examine the factors holding back the adoption of AWD, Direct-Seeded Rice (DSR), and improved Rice Straw Management (RSM). We also assessed how market-based approaches, especially carbon credit incentives, could help speed up CSA adoption."